Muscle and joint force dependence of scaling and skill level of athletes in high-speed overhead task: Musculoskeletal simulation study. (2020) - Barnamehei, Hamidreza; Tabatabai Ghomsheh, Farhad; Safar Cherati, Afsaneh; Pouladian, Majid
Abstract: The badminton overhead forehand smash (OFS) is a high-speed overhead task in which various muscle-tendon units generate the forces of motion. It is impossible to examine all muscles and joints forces during the motion directly. The goals of the current study were: (1) to estimate the muscle and joint load during OFS, (2) to compare results between generic and scaled-generic models. 20 badminton athletes categorized to two amateur and professional groups. A motion analysis system was used to record the marker trajectories. The shoulder musculoskeletal model developed in OpenSim which includes 5 segments, 10° of freedom, 26 muscle-tendon units. The inverse kinematics was used to evaluate joint kinematics during OFS. The static optimization and joint reaction force tools were utilized to estimate the joint and muscles forces through the OFS, respectively. Results present the joint and muscles forces pattern through the OFS for amateur and professional players. Significant differences were detected between generic and scaled-generic musculoskeletal models in the majority of muscles and joints forces. In addition, significant differences were found between amateur and professional athletes during OFS. The muscle and joint forces results are useful for athletes, coaches, trainer, and sports medicine. Recognition of which muscles and how to play an effective role to produce the force on the correct direction is vital for coaches and trainers due to design effective training to enhance the performance of athletes. On the other hand, the pattern of joint loads may help to evaluate which joints and in which sequences are high-risk. This study is a first and comprehensive study that examine the overhead high-speed motion in two different skill levels.